ChemInform Abstract: Synthesis and Characterization of Schiff Base Complex of Pd(II) Supported on Superparamagnetic Fe3O4@SiO2 Nanoparticles and Its Application as an Efficient Copper‐ and Phosphine Ligand‐Free Recyclable Catalyst for Sonogashira—Hagihara Coupling Reactions. Issue 30 (29th July 2014) - Esmaeilpour, Mohsen; Sardarian, Ali Reza; Javidi, Jaber
Abstract The heterogeneous catalyst is easily removed by means of an external magnet and reused six times without significant loss of activity.